COMPUTER PRODUCTIVITY EVALUATION - Lastovskis, Andris; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Computer productivity evaluation also known as benchmarking is the act of running a computer program, a set of programs, or other operations, in order to assess the relative performance of an object, normally by running a number of standard tests and trials against it. The term 'benchmark' is also mostly utilized for the purposes of elaborately designed benchmarking programs themselves. Benchmarking is usually associated with assessing performance characteristics of computer hardware, for example, the floating point operation performance of a CPU, but there are circumstances when the technique is also applicable to software. Software benchmarks are, for example, run against compilers or database management systems. Benchmarks provide a method of comparing the performance of various subsystems across different chip/system architectures. Test suites are a type of system intended to assess the correctness of software. [1] Many components in a system contribute to its overall performance, but the CPU/processor, memory, graphics board, and storage configuration generally play the largest roles for most users. Which of these components is the most important in a particular case depends on the individual person's usage patterns. [2]